Mrs. Benedict Arnold : a novel - Parry, Emma (Zando, 2026)
A riveting reimagining of the young woman who almost ended the American Revolution. Philadelphia in the 1770s. Peggy Shippen longs for the war she's living through to end. Though not always appreciated at home, she finds her curiosity is welcomed by a lively and influential circle of friends, including a glamorous rising star in the British army, Captain John Andre. When the war separates them, Peggy is devastated--both by his absence and the horrors of ongoing conflict--before finding consolation in a man whose heroics for the Patriots have captured the world's imagination: General Benedict Arnold. As she trades Loyalist balls for Patriot salons, entertaining the most prominent figures of early America, and navigating the country's lethal political currents, she conceives of an audacious scheme to achieve peace and her family's survival, unleashing what would become the most famous act of treason in history.When uncertainty and bloodshed are the only constants, Mrs. Benedict Arnold asks, how far will one woman go for safety?